A taxonomy of control mechanisms and effects on channel cooperation in China - Luo, Yadong; Liu, Y.; Zhang, L.; Huang, Y. (Springer, 2011)
This study identifies variations of contractual and relational control mechanisms used in governing channel relationships and explores how such variations are related to channel cooperation. Building on the loose coupling logic, assuming that control and cooperation coexist in any loosely structured partnership, we develop a taxonomy that illustrates four metaphorical situations, each respectively indicating a varying degree of control and related cooperative behaviors, in buyer-supplier relationships. We use matched manufacturer-distributor data from China to test theorized configurations through cluster analysis. The results validate the matrix of control mechanisms we proposed and confirm a systematic configuration between each metaphorical situation in the control taxonomy and corresponding cooperative behaviors in commitment, information sharing, compliance to power execution, and dependence continuity.